KOMUNITAS ASCIDIA DI PESISIR MALALAYANG DUA, TELUK MANADO, SULAWESI UTARA - Adrianus Malintoi; Inneke F M Rumengan; Kakaskasen A Roeroe; Veibe Warouw; Ari B Rondonuwu; Medy Ompi (Sam Ratulangi University, 2020)
Field survey on ascidian community was conducted along the coastal area of Malalayang Dua in order to find out species of ascidia, species abundance, and ascidian substrates. A survey method and quadrant transects were applied. Pictures were taken, while species and their substrates were sampled. Species identification was based on morphological characteristics, while substrate type identification was based on ascidian species attachment. The results shows that 21 ascidian species were found in the the coastal of Malalayang Dua. Didemnum molle was the highest abundant species in the area, followed by Polycarpa aurata, Polycarpa sp.4. and Polycarpa sp.2.. Dead coral algaes (DCA) were found to be the most preferred substrates by ascidians in the area. Keywords : ascidia, species, substrate, distribution, and abundance Survei lapangan terhadap komunitas ascidia dilakukan di pesisir Malalayang Dua untuk mendapatkan data jenis, kelimpahan, dan substrat ascidia. Metode yang digunakan yaitu metode survei jelajah dan transek kuadran. Identifikasi jenis ascidia dilakukan berdasarkan karakteristik morfologi. Hasil penelitian ditemukan ada 21 jenis ascidia. Substrat jenis death coral algae (DCA) merupakan substrat yang paling banyak ditempati ascidia. Kelimpahan ascidia tertinggi adalah Didemnum molle di pesisir Malalayang Dua, diikuti oleh Polycarpa aurata, Polycarpa sp.4. dan Polycarpa sp.2. Death coral alga (DCA) ditemukan sebagai substrat yang paling disukai oleh ascidia di daerah itu. Kata Kunci : ascidia, spesies, substrat, distribusi, dan kelimpahan